A study of coal aggregation by standing-wave ultrasound. (15th July 2019) - Chen, Yuran; Xie, Guangyuan; Chang, Jing; Grundy, James; Liu, Qingxia
Abstract: Recovery of fine coal particles by flotation has always been difficult due to the low collision efficiency between air bubbles and fine coal particles. One method to improve the flotation recovery of fine coal particles is the aggregation of these particles prior to the flotation process. This paper introduces a new method for the aggregation of fine coal particles by utilizing an ultrasonic standing-wave treatment. Under a 200 kHz ultrasonic standing-wave, cavitation bubbles formed on the hydrophobic coal particle surfaces. The bubble-laden coal particles moved to the nodes of the ultrasonic standing wave by the acoustic radiation force if the size of the cavitation bubbles were larger than the resonance radius, resulting in rapid aggregation of the fine coal particles. Micro-flotation results indicated that the flotation rate significantly increased after the ultrasonic standing-wave treatment. This study demonstrated an efficient ultrasonic standing-wave method for improving the flotation rate of fine coal particles without addition of chemicals or collectors.